Microwave-Assisted Rapid Synthesis of Magnetite Fe3O4 Nanoparticles - Deng, Chonghai; Hu, Hanmei; Ge, Xinqing; Han, Chengliang; Zhao, Difang (Asian Journal of Chemistry, 2013)
Using FeSO4(NH4)2SO4·6H2O and triethanolamine as iron and alkali sources, magnetite Fe3O4 nanoparticles are synthesized through a microwave-assisted chemical route. The as-prepared products are characterized by X-ray diffraction, field-emission scanning electron microscopy and transmission electron microscopy. The sizes of Fe3O4 nanoparticles ranging from 5 to 20 nm are obtained. The magnetic property of the obtained Fe3O4 nanoparticles is studied by vibrating sample magnetometer. Magnetic analysis reveals that the Fe3O4 nanoparticles are ferromagnetic with a saturation magnetization of 25.5 emu·g-1. The growth mechanism of Fe3O4 nanoparticles is also simply discussed.